Changes in Segmental Impedances and Selected Body Composition Parameters Assessed by Multi-Frequency Bioimpedance Analysis after Fluid Consumption in Healthy Young Population - Forejt, Martin; Pokorová, Kateřina; Uher, Michal; Novák, Jan; Čermáková, Erika (International journal of medical sciences, 2023)
Objectives: Body composition (BC) analysis is a routine part of comprehensive public health care. Assessment of BC is more important source of information than BMI. Adherence to the standard measurement conditions is essential for the correct results. Our study aimed to examine the effect of acute fluid consumption on measures of body mass (BM), percentage of body fat (%BF), visceral fat (VF), percentage of body water (%BW), and impedance at 100 kHz (I100) and 20 kHz (I20) using segmental multi-frequency bioelectrical impedance analysis (SMF-BIA) in a general healthy population. Methods: 95 consecutive healthy normal-weight adults (42 men; 53 women) were involved in the study (mean ± s.d.; age 23.9±1.6 years; body mass 68.3±14.1 kg). All subjects underwent two separate series of body composition (BC) measurements at 0 (BASELINE), 30, 60, 90 min (POST): the first series after drinking 600 ml of isotonic carbohydrate/electrolyte drink (IST) and the second after no fluid administration (CON). Individual measurements were performed in the morning on two consecutive days. Results: In the IST group, BM, VF (both P<0.001), and %BF (P<0.05) increased significantly at 30 min POST compared to BASELINE. BM and VF remained elevated at 90 min POST (both P<0.001). %BW decreased significantly at 30 min POST (P<0.01) then increased at 60 min (P<0.001) and 90 min (P<0.01) POST. There were no significant changes in I100. I20 increased significantly at 30 min POST (P<0.001) then decreased at 60 min (P<0.001) and 90 min POST (P<0.01) compared to BASELINE. In the CON group, BM and VF decreased below BASELINE at 90 min POST (P<0.001), %BF, %BW and I100 did not change significantly. The difference between IST and CON was statistically significant for all POST measurement times only in BM and VF (both P<0.001). The VF results are also underlined by the detected impedance changes in the trunk area at 20 kHz (B20) and 100 kHz (B100) at 60 min and 90 min (both P<0.001). Conclusions: Our study suggests that segmental impedances and BC measurement in healthy young normal-weight adults requires strict adherence to fluid restriction at least 90 min before the measurement to avoid false impedance values and overestimation of BM and VF.
Keywords: Young Adult; Electric Impedance; percentage of body fat; elektrolyty; Male; absorpční fotometrie; acute fluid consumption; mladý dospělý; elektrická impedance; tuková tkáň; Adult; dospělí; mužské pohlaví; Food; potraviny; adults; body composition changes; segmental multi-frequency bioelectrical impedance analysis; visceral fat; lidé; Adipose Tissue; ženské pohlaví; Humans; Body Mass Index; složení těla; Body Composition; index tělesné hmotnosti; Female; Absorptiometry, Photon; Electrolytes